Successes and Hurdles in Stem Cells Application and Production for Brain Transplantation - Henriques, Daniel; Moreira, Ricardo; Schwamborn, Jens; Pereira de Almeida, Luís; Mendonça, Liliana S. (Frontiers in Neuroscience, 2019)
Brain regenerative strategies through the transplantation of stem cells hold the potential to promote functional rescue of brain lesions caused either by trauma or neurodegenerative diseases. Most of the positive modulations fostered by stem cells are fueled by bystander effects, namely increase of neurotrophic factors levels and reduction of neuroinflammation. Nevertheless, the ultimate goal of cell therapies is to promote cell replacement. Therefore, the ability of stem cells to migrate and differentiate into neurons that later become integrated into the host neuronal network replacing the lost neurons has also been largely explored. However, as most of the preclinical studies demonstrate, there is a small functional integration of graft-derived neurons into host neuronal circuits. Thus, it is mandatory to better study the whole brain cell therapy approach in order to understand what should be better comprehended concerning graft-derived neuronal and glial cells migration and integration, before we can expect these therapies to be ready as a viable solution for brain disorders treatment. Therefore, this review discusses the positive mechanisms triggered by cell transplantation into the brain, the limitations of adult brain plasticity that might interfere with the neuroregeneration process, as well as some strategies tested to overcome some of these limitations. It also considers the efforts that have been made by the regulatory authorities to lead to better standardization of preclinical and clinical studies in this field in order to reduce the heterogeneity of the obtained results.